Association of Obstetric Risk Factors with Postpartum Urine Retention in Spontaneous Labor: Hubungan Faktor Risiko Obstetrik dengan Retensio Urin Postpartum pada Persalinan Spontan - Pribakti Budinurdjaja; Ihya R. Nizomy; Hermin Sabaruddin (Indonesian Socety of Obstetrics and Gynecology, 2021)
Objective: To determine the relationship between obstetric risk factors and the incidence of postpartum urinary retention in spontaneous labour at RSUD Ulin Banjarmasin.Methods: This clinical study used an analytical observational design with a cross-sectional approach. The population of this study was patients with a diagnosis of postpartum urinary retention in spontaneous labour in the delivery ward and postpartum ward of Ulin Banjarmasin Hospital between January 2018-January 2020. The sample for this study was a part of the target population selected by purposive sampling, which fulfilled the inclusion and exclusion criteria. Data were analyzed using the Chi square test and multivariate analysis using binary logistics.Results: The results showed 35 samples of patients diagnosed with postpartum urinary retention in spontaneous labour and had met the inclusion and exclusion criteria. Characteristic data of the study samples found that most of the study subjects were more than 35 years old, 27 patients (77%), 21 patients (60%) of cases with primigravida parity, 26 patients (76%) with the duration of second stage labour more than equal to 1 hour. Episiotomy was performed in 30 patients (86%), 34 patients (97%) had a newborn birthweight of less than 4000 grams. There was a significant association between the risk factors for parity in primigravida (p-value 0.02), second stage labour duration in primigravida (p-value 0.01), and episiotomy (p-value 0.01), with postpartum urinary retention in spontaneous labour. In contrast, age (p-value 0.19), and birthweight (p-value 0.10) were not significantly associated with postpartum urinary retention in spontaneous labour.Conclusions: There were significant associations between obstetric risk factors (parity, duration of second stage labour, and episiotomy) with postpartum urinary retention in spontaneous labour. Whereas age and birth weight were not significantly associated with postpartum urinary retention in spontaneous labour.Keywords: obstetric risk, postpartum retention, spontaneous delivery. Abstrak Tujuan: Mengetahui hubungan faktor risiko obstetrik dengan kejadian retensio urin postpartum pada persalinan spontan di RSUD Ulin Banjarmasin.Metode: Penelitian ini merupakan penelitian klinis dengan rancangan observasional analitik dengan pendekatan potong lintang. Populasi dari penelitian ini adalah ibu postpartum yang didiagnosis dengan retensio urin postpartum pada persalinan spontan di kamar bersalin dan di ruangan nifas RSUD Ulin Banjarmasin periode Januari 2018-Agustus 2020. Data dianalisis bivariat menggunakan uji Chi square dan analisis multivariate dengan menggunakan binary logistik.Hasil: Didapati 35 sampel yang didiagnosis retensio urin postpartum pada persalinan spontan dan memenuhi kriteria inkulusi dan eksklusi. Data karakteristik sampel penelitian ditemukan usia terbanyak subyek penelitian berusia lebih dari 35 tahun sebanyak 27 pasien (77,14%), kasus dengan paritas primigravida sebanyak 21 pasien (60%), lama kala dua primigravida lebih dari sama dengan 1 jam sebanyak 26 pasien (76%). Tindakan episiotomi sebanyak 30 pasien (86%), berat bayi lahir terbanyak pada berat kurang dari 4.000 gram yaitu sebnyak 34 pasien (97%). Terdapat hubungan yang bermakna pada faktor risiko paritas pada primigravida dengan p value 0,02, lama kala dua dengan p value 0,01, dan tindakan episotomi dengan p value 0.01 dengan kejadian retensio urin postpartum sedangkan didapatkan hasil yang tidak bermakna pada risiko obstetrik usia dengan p value 0.19 dan berat bayi lahir dengan p value 0.10 pada kejadian retensio urin postpartum.Kesimpulan: Terdapat hubungan signifikan antara faktor risiko obstetrik (paritas, lama kala dua dan tindakan episotomi) dengan retensio urin postpartum persalinan spontan. Sedangkan umur dan berat badan lahir tidak berhubungan dengan retensio urin postpartum pada persalinan spontanKata kunci: persalinan spontan, risiko obstetrik, retensio postpartum.